ZUM FREMDSPRACHLICHEN SCHREIBEN VOR DEM HINTERGRUND DER EINZELNEN SPRACHFERTIGKEITEN AM BEISPIEL DES DEUTSCHUNTERRICHTS AUF DER FORTGESCHRITTENENSTUFE - Pawłowska, Agnieszka (Acta Neophilologica, 2013)
The article is an attempt to answer a question whether writing in a foreign language is a genuine challenge, a support in (educational) everyday reality, or solely a separate activity of secondary importance. Writing in a foreign language is considered here from the perspective of other language skills, followed by an analysis of a questionnaire conducted among students of School of German examining the importance and level of difficulty attached by them to individual skills.